2022
DOI: 10.1101/2022.03.16.484616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-exposure to mRNA-LNP inhibits adaptive immune responses and alters innate immune fitness in an inheritable fashion

Abstract: Billions of SARS-CoV-2 mRNA-LNP vaccine doses have already been administered to humans. However, we lack a comprehensive understanding of the immune effects of this platform. Here we bring experimental evidence that pre-exposure to mRNA-LNPs or its LNP component has effects on both innate and adaptive immune responses. Pre-exposure to mRNA-LNPs led to long-term, platform-specific inhibition of the adaptive immune responses. As such, mice responded with lower antibody responses when exposed the second time to t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…In addition, the surface of LNPS is often modified with PEG, which can improve their blood circulation time and reduce their chance of being cleared by the immune system. LNPs have multiple advantages in RNA vaccine delivery [135][136][137] . Their lipid bilayer structure can effectively encapsulate mRNA vaccines and protect them from degradation by the external environment, which helps to improve the stability of mRNA.…”
Section: Structure and Characteristics Of Lnpsmentioning
confidence: 99%
“…In addition, the surface of LNPS is often modified with PEG, which can improve their blood circulation time and reduce their chance of being cleared by the immune system. LNPs have multiple advantages in RNA vaccine delivery [135][136][137] . Their lipid bilayer structure can effectively encapsulate mRNA vaccines and protect them from degradation by the external environment, which helps to improve the stability of mRNA.…”
Section: Structure and Characteristics Of Lnpsmentioning
confidence: 99%
“…If you take these LNPs and mix them with proteins, you obtain similar immune responses to the mRNA-LNP [ 49 ]. Thus, the critical component here is the LNP with ill-defined biological effects but strong adjuvant and inflammatory properties, which likely also contribute to the immune system’s reprogramming [ 50 , 51 ]. While the positive aspect of this platform is widely publicized, the authorities seem to not be concerned by the severe side effects and thousands of deaths reported so far for this platform in the Vaccine Adverse Event Reporting System (VAERS) database [ 52 ].…”
Section: All That Glitters Is Not Goldmentioning
confidence: 99%
“…In a mouse model, Qin et al showed that mRNA-LNP pre-exposure can alter immune responses to influenza and C. albicans infection [6]. These results collectively demonstrate that the effects of the BNT162b2 vaccine go beyond the adaptive immune system and can also modulate innate immune responses.…”
mentioning
confidence: 94%
“…While the induction of specific immunity against SARS-CoV-2 has been intensively studied, much less is known about the effects of this new class of mRNA vaccines against heterologous pathogens. The lipid nanoparticle (LNP) component of those vaccines was reported to induce strong pro-inflammatory responses [4], and recent studies have shown that BNT162b2 can also induce long-term transcriptional changes in myeloid cells [5,6]. This suggests that the response of immune cells against various microorganisms other than SARS-CoV-2 could also change after BNT162b2 vaccination.…”
Section: Introductionmentioning
confidence: 99%